Strategic Issue Management Systems: Forms, Functions, and Contexts - Dutton, Jane E.; Ottensmeyer, Edward J. (Academy of Management Review, 1987)
Organizations use strategic issue management (SIM) systems to enhance their capacity to adapt. Despite increasing prominence, very little is Known about the design and use of these systems. This paper presents typologies of the forms SIM systems can take and the functions SIM systems can serve. It describes how pressures imposed by different contexts affect both the form and function of SIM systems. Implications for theory and practice are discussed.